A Systems Pharmacology Approach Uncovers Wogonoside as an Angiogenesis Inhibitor of Triple-Negative Breast Cancer by Targeting Hedgehog Signaling. Issue 8 (15th August 2019) - Huang, Yujie; Fang, Jiansong; Lu, Weiqiang; Wang, Zihao; Wang, Qi; Hou, Yuan; Jiang, Xingwu; Reizes, Ofer; Lathia, Justin; Nussinov, Ruth; Eng, Charis; Cheng, Feixiong
Summary: Triple-negative breast cancer (TNBC) is an aggressive and heterogeneous disease that lacks clinically actionable genetic alterations that limit targeted therapies. Here we explore a systems pharmacology approach that integrates drug-target networks and large-scale genomic profiles of TNBC and identify wogonoside, one of the major active flavonoids, as a potent angiogenesis inhibitor. We validate that wogonoside attenuates cell migration, tube formation, and rat aorta microvessel outgrowth, and reduces formation of blood vessels in chicken chorioallantoic membrane and TNBC cell-induced Matrigel plugs. In addition, wogonoside inhibits growth and angiogenesis in TNBC cell xenograft models. This network-based approach predicts, and we empirically validate, wogonoside's antiangiogenic effects resulting from vascular endothelial growth factor secretion. Mechanistically, wogonoside inhibits Gli1 nuclear translocation and transcriptional activities associated with Hedgehog signaling, by promoting Smoothened degradation in a proteasome-dependent mechanism. This study offers a powerful, integrated, systems pharmacology-based strategy for oncological drug discovery and identifies wogonoside as a potential TNBC angiogenesis inhibitor. Graphical Abstract: Highlights: A systems pharmacology approach uncovers wogonoside as a TNBC angiogenesis inhibitor Network analysis identifies that wogonoside inhibits VEGF expression in TNBC Wogonoside inhibits the Gli1 nuclear translocation and transcription activities Wogonoside promotes Smoothened (SMO) degradation in a proteasome-dependent mechanism Abstract : Huang et al., introduce a systems pharmacology approach and identify wogonoside as an effective angiogenesis inhibitor in triple-negative breast cancer (TNBC) in vitro and in vivo . Mechanistically, the authors demonstrate that wogonoside inhibits the Gli1 nuclear translocation and transcription activities of Hedgehog signaling via specifically promoting ubiquitination-dependent degradation of Smoothened.